DEVELOPING THE ENGLISH SPEAKING MATERIAL FOR BASIC OF CRUISE SHIP CREW OF STUDENTS AT BANGKALAN EDUCATION CENTER - Roziyan Adi Wicaksana (Graduate Program, University of Islam Malang, 2020)
Barely, availability of the appropriate English materials is much needed for the students to master the English optimally. The primary goal of this research is to guide students to be able to communicate in English through the appropriate materials for basic of cruise ship crew. Teaching and learning of English at this subject was considered unable to achieve its objective. The main problem was that there were not instructional materials to support the teaching learning process. The procedures being employed in this study were R&D. Collecting relevant information for a basis of developing materials, the interview with the 1 teacher and 5 students, and classroom observation were carried out to complete the information provided in the instructional materials at Bangkalan Education Center. The findings represented that the respondents showed good responses in attractiveness of the materials, level of difficulties, steps of activities, usefulness of the materials in supporting speaking practice and students’ worksheet and the materials was considered eligible. Moreover, the materials were great in facilitating the students to practice their oral language. This study then ends with suggestion for teacher and other researchers.Keywords: Cruise Ship, Material Development, English for Specific Purpose.